Overview of Knowledge Levels and Risk Factors for Scabies and Pediculosis capitis among Female Students in Darularafah Raya Islamic Boarding School - Bella Yofrisanda; Dewi Saputri; Makmur Sitepu; Milahayati Daulay (Talenta Publisher, 2025)
Background: Scabies and pediculosis capitis infections remain common parasitic issues, particularly in densely populated living environments such as boarding schools. The high incidence of these infections is influenced by the level of knowledge and risk-related behaviors within the population. Objective: This research was conducted to understand the level of knowledge and risk factors for scabies and pediculosis capitis infections among female students at Darularafah Raya Islamic Boarding School. Methods: This descriptive research was conducted with eleventh-grade female students, with a sample size of 58 participants selected using systematic random sampling techniques. Data were collected through questionnaires assessing knowledge levels and risk factors. Results: Research data indicate a prevalence of scabies of 22.4% and pediculosis capitis of 55.4%. A total of 31 respondents (53.4%) demonstrated a good level of knowledge about scabies, while 52 respondents (89.7%) showed a good level of knowledge about pediculosis capitis. The primary risk factors for scabies observed among respondents were sharing clothing and sharing beds. For pediculosis capitis, the prevalent risk factors include using communal prayer garments and sharing bedding equipment. Conclusion: Most respondents possess good knowledge; however, the incidence of scabies and pediculosis capitis infections remains relatively high.